2020
DOI: 10.1111/1365-2656.13175
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and translocation disrupt the relationship between host density and parasite abundance

Abstract: The species interactions that structure natural communities are increasingly disrupted by radical habitat change resulting from the widespread processes of urbanization and species translocations. Although many species are disadvantaged by these changes, others thrive in these new environments, achieving densities that exceed those in natural habitats. Often the same species that benefit from urbanization are successful invaders in introduced habitats, suggesting that similar processes promote these species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…In addition, although breeding occurs year-round, influxes of toads to French Guiana breeding sites occurred in December, indicating that toads may be more mobile during the wet season. This reliance on limited freshwater resources during the drier months may also explain why toads lived at such high densities at coastal sites, despite the fact that these dense populations suffered from high levels of parasitism as a result 40 . Limited rainfall during the tracking period may therefore have restricted toad movements, especially at coastal sites, where seasonality is more pronounced and water availability was limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, although breeding occurs year-round, influxes of toads to French Guiana breeding sites occurred in December, indicating that toads may be more mobile during the wet season. This reliance on limited freshwater resources during the drier months may also explain why toads lived at such high densities at coastal sites, despite the fact that these dense populations suffered from high levels of parasitism as a result 40 . Limited rainfall during the tracking period may therefore have restricted toad movements, especially at coastal sites, where seasonality is more pronounced and water availability was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of native-range toads has shown great flexibility in movement patterns in response to local conditions. Toads in the native range exploit a wide range of habitats, including beach and rainforest sites otherwise typified by profoundly disparate faunal groups, exhibiting a level of habitat generalism that likely facilitated this toad’s success and subsequent colonization of a wide range of habitats in their introduced range 40 , 62 , 64 . Native-range toads also exhibited strong behavioural plasticity in response to environmental conditions and utilized different strategies to exploit available resources in different habitats; such plasticity may also increase performance in species invading novel environments 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collection of Australian cane toads took place between May 2014 and December 2018 in the Northern Territory (NT; n =7 toads), Queensland (QLD; n =51), and Western Australia (WA; n =49; Supplementary Table S1 ). Between August and November 2017, French Guianese toads were collected near Regina and St. George ( Supplementary Table S1 ; DeVore et al, 2020 ). Hawai’ian cane toads ( n =10) were collected from two regions on the island of O’ahu in June 2015 ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%